Analisis Kemiskinan Energi Pada Tingkat Provinsi Tahun 2015-2023 di Indonesia - Azhary, Putri Asyar; Irfan, Muhammad (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
The purpose of this study is to ascertain and examine how Indonesian energy poverty is impacted by per capita income, economic disparity, industrialization, and investment. The research variables in this study are divided into two categories: the independent variables are per capita income, income inequality, industrialization, and investment, and the dependent variable is energy poverty. The study uses secondary data from the Central Bureau of Statistics of Indonesia. utilizing a cross section of 34 Indonesian provinces and a time series spanning 2015–2023, this study employs panel data regression analysis utilizing the Random Effect Model (REM) approach. According to the study's findings, (1) Indonesia's energy poverty is significantly and negatively impacted by per capita income. On the other hand, energy poverty is positively and significantly impacted by income inequality. Then (3) Indonesia's energy poverty is significantly and negatively impacted by industrialization. Additionally, investment has a minor but positive impact on Indonesia's energy poverty.